Determinants of long-acting contraceptives use among reproductive-age couples in Tanjung Karang Public Health Centre Mataram City, West Nusa Tenggara - Widya Aryati; Dewa Nyoman Wirawan; Komang Ayu Kartika Sari; Anak Agung Sagung Sawitri (Universitas Udayana, 2018)
Background and purpose: The national family planning program prioritises the use of long-acting contraceptives which include intrauterine devices (IUD), tubectomy, vasectomy, and implant. However, the coverage of long-acting contraceptives in Indonesia remains low. This study aims to identify the determinants of longacting contraceptives uptake among reproductive-age couples in Tanjung Karang Public Health Centre (PHC) Mataram City. Methods: A cross-sectional study was conducted involving 169 reproductive age couples in Tanjung Karang PHC in 2016. Samples were selected from six sub-villages (dusun) in two villages using systematic random sampling. We selected 85 samples from coastal and 84 samples from non-coastal areas. Data on sociodemographic characteristics, perception, husband support, access to service, and information regarding long-acting contraceptives were collected through home interview. Analysis with logistic regression was applied to determine the factors influencing long-acting contraceptives uptake. Results: The majority of respondents aged 20–35 years-old, and most of them have a lower level of education and knowledge regarding longacting contraceptives. Among all current users, as many as 37.0% use long-acting contraceptive methods. The respondents refused to use long-acting contraceptives due to prohibited by the husband (92.8%) and desire to have more children (38.7%). Multivariate analysis using logistic regression showed that the uptake of long-acting contraceptives was significantly associated with area of residence (noncoastal) with an adjusted odds ratio (AOR)=2.89 (95%CI; 1.39-6.01), employment status with AOR=0.40 (95%CI; 0.18-0.90), income at minimum wages and above with AOR=2.47 (95%CI; 1.16-5.26), and husband support with AOR=2.19 (95%CI; 1.18-3.41). Conclusions: The use of long-acting contraceptives are associated with husband support, living in non-coastal areas, and having a higherincome. Ongoing support from the husband, especially among those who live in coastal areas and from the lower socioeconomic background, is required to improve the coverage of long-acting contraceptives.